An Introduction of Multiple P-adic Data Type and Its Parallel Implementation - Lu, Chao; Li, Xinkai (The International journal of networked and distributed computing (Online), 2015)
Our research group has been working on the P -adic theory and its implementation. Based on the Chinese Remainder theorem and the Hensel code a new data type, called Multiple P-adic Data Type, has been established to realize rational calculation. With this data type all rational number operations are converted to integer calculations, and the fast integer multiplication of modern computer architectures can be fully taken advantage of. This data type can be significantly effective in the parallel and cloud computing environment due to its independent computation at each node during the calculation process.